Climate change accelerates range expansion of the invasive non-native species, the Pacific oyster, Crassostrea gigas. (13th December 2020) - King, Nathan G; Wilmes, Sophie B; Smyth, David; Tinker, Jonathan; Robins, Peter E; Thorpe, Jamie; Jones, Laurence; Malham, Shelagh K
Abstract: Invasive non-native species and global warming are two of the greatest components of global ecosystem change. The Pacific oyster, Crassostrea gigas, is the world most cultivated shellfish and was introduced throughout the Northwest European Shelf (NWES) under the premise it could not complete its life cycle. Recent warming trends have changed this and wild populations can be found as far north as Nordic Scandinavia. Under the RCP8.5 concentration pathway, we predict that the majority of NWES coastline will be within C. gigas 's thermal recruitment niche by 2100. Given the widespread occurrence of current naturalized C. gigas populations, its large larval dispersal potential and a lack of feasible management solutions, C. gigas will likely undergo a considerable range expansion this century. The time taken to reach maturity is predicted to decrease by up to 60 days, which may lead to precocious spawning events, facilitating expansion further. Crassostrea gigas can form extensive reefs completely transforming native systems. This may compromise native biodiversity, protected habitats, and commercial species. However, naturalization can also deliver a number of beneficial ecosystem goods and services to human society. Whether naturalization is deemed positive or negative will depend on biogeographic context, the perceptions of stakeholders, and the wider management priorities.